2018
DOI: 10.1590/s1984-296120180011
|View full text |Cite
|
Sign up to set email alerts
|

Control of sheep gastrointestinal nematodes using the combination of Duddingtonia flagrans and Levamisole Hydrochloride 5%

Abstract: The objective was to evaluate the action of D. flagrans pellets in association with Levamisole Hydrochloride 5% for controlling sheep gastrointestinal nematodes in the northeastern Brazil. Three groups of six sheep each were formed: group 1 received 3 g of the pellets (0.6 g of D. flagrans mycelium) for each 10 kg b.w., twice a week for six months, and deworming with Levamisole Hydrochloride 5% when EPG ≥ 1500; group 2 received a dosage of Levamisole Hydrochloride 5% when EPG ≥ 1500; and group 3 received 3 g o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…The D. flagrans group showed low EPG values throughout the experiment (p < 0.05), with the parasite load on day 120 being 92% lower than that in the control group. A reduction in small ruminant EPG, although lower than that noted in the present study, was observed by Vilela et al (2012), Vilela et al (2013), Vilela et al (2016) and Vilela et al (2018) after the use of pellets of nematophagous fungi in the Northeastern semiarid region. However, these animals were kept in an extensive regime and fed on pasture native to the Caatinga, which increased reinfection rates.…”
Section: Discussioncontrasting
confidence: 85%
“…The D. flagrans group showed low EPG values throughout the experiment (p < 0.05), with the parasite load on day 120 being 92% lower than that in the control group. A reduction in small ruminant EPG, although lower than that noted in the present study, was observed by Vilela et al (2012), Vilela et al (2013), Vilela et al (2016) and Vilela et al (2018) after the use of pellets of nematophagous fungi in the Northeastern semiarid region. However, these animals were kept in an extensive regime and fed on pasture native to the Caatinga, which increased reinfection rates.…”
Section: Discussioncontrasting
confidence: 85%
“…Vilela et al . (2018) reported the coadministration of pellets containing D . flagrans and levamisole to control sheep parasites, and levamisole is used as a deworming agent when the EPG of sheep feces exceeds 1500.…”
Section: Resultsmentioning
confidence: 99%
“…The use of biological control by helminthophagous fungi provides an option to reduce the rates of contamination by larvae and, consequently, less reinfection for the animals, enabling them to develop natural immunity against the helminths. In addition, animals that receive helminthophagous fungi have higher weight gain rates, higher globular volume percentages, and lower EPG values when compared to those that do not receive the fungi [5,[67][68][69][70]. In grazing horses that received D. flagrans chlamydospores daily, strongylide counts below 200 EPG were obtained for 16 months, also verifying that they recovered normal blood values of erythrocytes, hemoglobin, and hematocrit [71].…”
Section: Advances In the Control Of Gastrointestinal Nematodes In Pasture Animalsmentioning
confidence: 77%